A Novel Method for the Localization and Management of Traumatic Cyclodialysis Cleft. (11th March 2014) - Wang, Mingling; Hu, Shufang; Zhao, Zhenquan; Xiao, Tianlin
Abstract : Purpose. To propose a novel surgical method for the localization and management of traumatic cyclodialysis clefts. Methods. Five patients with traumatic cyclodialysis clefts who underwent the innovative surgery were retrospectively reviewed. The new method was introduced to repair a cyclodialysis cleft with two running sutures from the middle to each end of the cleft under the guidance of a probe. Preoperative and postoperative visual acuity (VA), intraocular pressure (IOP), slit lamp and gonioscopic results, ultrasound biomicroscopy (UBM), and optical coherence tomography (OCT) findings were recorded. Results. Cyclodialysis clefts were completely closed postoperatively in four patients (four eyes); this was confirmed by progressively improved VA, restoration into the normal range of the IOP, disappearance of suprachoroidal fluid, and reduced macular edema. Only one patient with multiple clefts had an incomplete reattachment. Conclusions. This clinical study offers a novel and efficient method to localize and repair the cyclodialysis clefts.